Clinical features and genetic background of the sympatric species Paracoccidioides brasiliensis and Paracoccidioides americana - de Macedo, Priscila Marques (PLoS Negl Trop Dis, 2019)
INTRODUCTION: The agents of paracoccidioidomycosis, historically identified as Paracoccidioides brasiliensis, are in fact different phylogenetic species. This study aims to evaluate associations between Paracoccidioides phylogenetic species and corresponding clinical data. METHODS: Paracoccidioides strains from INI/Fiocruz patients (1998–2016) were recovered. Socio-demographic, epidemiological, clinical, serological, therapeutic and prognostic data of the patients were collected to evaluate possible associations of these variables with the fungal species identified through partial sequencing of the ADP-ribosylation factor (arf) and the 43-kDa-glycoprotein (gp43) genes. RESULTS: Fifty-four fungal strains were recovered from 47 patients, most (72.3%) infected in Rio de Janeiro state, Brazil. Forty-one cases were caused by Paracoccidioides brasiliensis and six by Paracoccidioides americana (former PS2). P. brasiliensis was responsible for severe lymph abdominal forms, whereas patients infected with P. americana presented a high rate of adrenal involvement. However, no statistically significant associations were found for all variables studied. P. americana presented 100% reactivity to immunodiffusion, even when tested against antigens from other species, while negative results were observed in 9 (20%) cases caused by P. brasiliensis, despite being tested against a homologous antigen. CONCLUSIONS: P. brasiliensis and P. americana are sympatric and share similar clinical features and habitat, where they may compete for similar hosts.